THE INFLUENCE OF PERCEPTION AND ATTITUDE TOWARDS THE CUSTOMER BEHAVIOUR IN USING SHARIA BANKING FINANCIAL SERVICES IN MEDAN - Azhmy, Muhammad Fauzan (NISBAH: Jurnal Perbankan Syariah, 2020)
The formation of perception will have an impact on the progress of Bank Syariah will also encourage people to be able to use the services of Bank Syariah as financial institutions. Lack of understanding and lack of education that they get gives different perceptions about Bank Syariah products, this is not in accordance with the real reality that Bank Syariah are banks that adopt Islamic Sharia values that forbid interest. Customer perception is closely related to attitude so that what is done by the customer is an objective reality that will influence their behaviour to use Bank Syariah services. The purpose of this study was to determine whether perceptions and attitudes affect the behaviour of entrepreneurs and employees in using sharia banking financial services. The sampling technique uses quota sampling. To conduct data analysis, data processing is carried out by using path analysis. The results of this study stated that partially perception variables significantly influence to the behaviour variables and attitude variables significantly influence to behaviour variables.